Knowledge, Attitude and Practice Towards Burn Patients Admitted in Madina Hospital Mogadishu Somalia - Farah, Osman Abdulle; Sönmez, Recep Erçin; Hassan, Mohamed Yusuf; Fıqı, Abdurrahman Osman; Alimoğlu, Orhan (International Journal of Human and Health Sciences (IJHHS), 2019)
Background : Burns are among the most devastating forms of trauma, and also the most common typesof injury affecting children in home environment. There are a major cause of morbidity and mortality all over the world for both children and adults,especiallyfor developing countries like Somalia because of inadequate medical treatment. Objective: The main objective is to gain knowledge, attitude andpractice towards burn patients admitted to Madina Hospital between October 2017 and October 2018. Methods: Throughout the study,researchers utilized both quantitative and qualitativemethods of data collection which were achieved from patients included in the study. A briefintroduction was made to the respondents before distributing the questionnaires with the explanation about thesignificance of the study. Results: 404 participants had been included in the study of which were divided into two groups such as ‘case’ (n=202) and ‘control’ (n=202) groups of each having equal number of patients. Burn injuries had beenfound most frequent in children less than 4 years of age (42.6%), and secondlyingadults between 20 and 40 years of age (38.6%). The male-female ratio had been found similar. Significant risk factors regarding burn injuries were such as; low level of education (OR=2.32, 95% CI: 1.28- 4.22, p<0.005),kerosene usage for cooking (OR=1.935; 95% CI:1.303–2.874, p<0.005) and lack of knowledgeconsideringprevention andsafety (OR=1.885, 5% CI:1.559-2.279, p<0.005). Conclusion: Ways of tackling the hazards posed by fire and othercauses of burns in homes, institutions and all work places should be taught in primary, secondary and tertiary levels of education. Low level of education as a risk factor for burns is a complex issue involving communities, non-governmental organizations and government. Theministry of education should incorporatehealth education in the curriculum of primary and secondary schools. International Journal of Human and Health Sciences Vol. 03 No. 04 October’19 Page : 218-222